2014
DOI: 10.1007/s11845-014-1149-5
|View full text |Cite
|
Sign up to set email alerts
|

The role of maternal screening in diagnosing congenital cytomegalovirus infections in highly immune populations

Abstract: According to our results, a maternal screening-based approach would be useful for only a very small group that is at risk of primary infection. Considering the cost of the scan, a routine maternal-based screening program is unadvisable in developing societies, but it is necessary for studies of different cohort groups and infectious diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
1
10

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 31 publications
1
7
1
10
Order By: Relevance
“…The frequency of maternal CMV viruria (9.2%) detected at the time of labor and delivery corresponds to rates reported in prior studies of healthy pregnant and nonpregnant women without HIV, which have ranged from 1.4-13% [14,17,20,22,30].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The frequency of maternal CMV viruria (9.2%) detected at the time of labor and delivery corresponds to rates reported in prior studies of healthy pregnant and nonpregnant women without HIV, which have ranged from 1.4-13% [14,17,20,22,30].…”
Section: Discussionsupporting
confidence: 82%
“…of the virus in urine specimens [13][14][15][16]. Although detection of CMV in bodily fluids may be a marker of viral replication [17], the majority of prior studies in healthy pregnant women have not shown that maternal CMV shedding in urine and/or cervical secretions is associated with an increased risk of cCMV in infants [14,16,[18][19][20][21][22].…”
mentioning
confidence: 99%
“…In our study, it was observed that seroprevalence of congenital CMV rates was in support of these classical data. Although high seroprevalence in society is thought to be protective for symptomatic infection, its efficacy for predicting long-term effects is limited (25). In the same study, the authors reported The study also showed a non-significant increase in adverse effects including preeclampsia and IUGR in HIG arm of the study population.…”
Section: Discussionmentioning
confidence: 88%
“…Konjenital CMV enfeksiyonu görülme sıklığı gelişmekte olan ülkelerde daha yüksek iken, gelişmiş ülkelerde düşük gelir gruplarında yüksek prevalans görülmektedir 4,6 . Siyahi ırk, düşük sosyoekonomik durum, prematüre doğum ve yenidoğan yoğun bakım ünitesinde yatmanın konjenital CMV enfeksiyonu için risk faktörleri olduğu bildirilmiştir 11 ğının araştırıldığı bir algoritmayı takip eden ve konjenital CMV enfeksiyonlarının gerçek prevalansını belirlemede eksik yönleri olan araştırmalardır 15,21 . İkinci grup çalışmalar ise prevalanstan ziyade ülkemizde görülen konjenital CMV olguları hakkında klinik ve nedensel bilgilerin sunulduğu olgu raporları veya serilerinden ibarettir [24][25][26] .…”
Section: Sitomegalovirüs Epidemiyolojisi Ve Türkiye'deki Durumunclassified